The Quranic approach in Taking Covenants from the Sons of Israel and the Impact of Breaking Them - Gaily, Afaf Makkawi Mohammed (Journal of Islamic Sciences, 2022)
This search aims at explaining the grounds and rules of divine approach in taking covenants from the sons of Israel and showing the impact of their breaking of covenants. In this search, the analytical descriptive methodology will be used, taking into account the nature of the research and its reliance on the main sources of the Quranic interpretations and viewing the commentaries of Quran interpreters.The search has reached a number of findings, of the most prominent are the following:1. The word “covenant” is mentioned repeatedly in the Glorious Quran with different meanings.2. The Glorious Quran has adopted a unique approach in addressing the sons of Israel, represented in the various styles that are in line with their attitudes and tendencies.3. The approach of the Quran is described of realism in addressing the issue of making covenants with the sons of Israel.4. Diversity of punishments resulted from the sons of Israel’s breaking of their covenants in certain verses (Ayahs) pertaining to them shows the retribution of breaking covenants in this life and the life to come.
Keywords: The Quranic approach; Covenants